1985
DOI: 10.1111/j.1432-1033.1985.tb09159.x
|View full text |Cite
|
Sign up to set email alerts
|

Human alpha-L-iduronidase. 2. Catalytic properties

Abstract: 1. The kinetic parameters of human liver a-L-iduronidase were determined with three disaccharide substrates: a-L-iduronosyl(l+4)2,5-anhydro-~-[l-~H]mannitol 6-sulphate, a-i,-iduronosyl(1+4)2,5-anhydro-~-[l-~H]mannitol and a-L-iduronosyl(1 + 3)2,5-anhydro-u-[l -3H]talitol 4-sulphate, derived from the natural substrates heparin and dermatan sulphate and one synthetic, fluorogenic substrate, 4-methylumbelliferyl a-L-iduronide.2. The enzyme activity with all four substrates was optimal at about pH 4.5. The K, valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 20 publications
(6 reference statements)
1
34
1
Order By: Relevance
“…In preliminary studies of the effect of ionic strength and buffer pH on subunit aggregation we were unable to alter the enzyme's native protein Mr. This result is different from a finding we have reported for z-L-iduronidase, another lysosomal enzyme involved in heparan sulphate degradation, in which buffer pH and ionic strength influenced subunit aggregation (Clements et al, 1985a). We reported previously that human liver sulphamate sulphohydrolase has a native protein Mr of 190000 and that higher enzymically inactive aggregates were also present (Mahuran et al, 1983a).…”
Section: Effect Of Salts and Substrate Analogues On Sulphamate Sulphocontrasting
confidence: 99%
See 1 more Smart Citation
“…In preliminary studies of the effect of ionic strength and buffer pH on subunit aggregation we were unable to alter the enzyme's native protein Mr. This result is different from a finding we have reported for z-L-iduronidase, another lysosomal enzyme involved in heparan sulphate degradation, in which buffer pH and ionic strength influenced subunit aggregation (Clements et al, 1985a). We reported previously that human liver sulphamate sulphohydrolase has a native protein Mr of 190000 and that higher enzymically inactive aggregates were also present (Mahuran et al, 1983a).…”
Section: Effect Of Salts and Substrate Analogues On Sulphamate Sulphocontrasting
confidence: 99%
“…Finally,-we have suggested that some or all of the eight enzymes involved in the degradation of the complex structured substrateheparan sulphatecouldby association with each other form an enzyme cluster (Clements et al, 1985a). This type of association would be expected to improve considerably the overall catalytic efficiency of the system by facilitated diffusion of the product of one enzyme that becomes the substrate for the next enzyme (Wombacher, 1983).…”
Section: Effect Of Salts and Substrate Analogues On Sulphamate Sulphomentioning
confidence: 99%
“…The biochemical confirmation was performed both in external accredited laboratories or in-house. In-house confirmation was done for IDUA (Anson, Bielicki, & Hopwood, 1992;Clements, Muller, & Hopwood, 1985), GAA (Beratis, LaBadie, & Hirschhorn, 1978) and GBA (Beutler & Kuhl, 1970). Briefly, for IDUA and GBA activity measurements, peripheral blood leukocytes were used and were extracted by adding 2 ml of a 2% dextran solution to 5 ml of blood sample.…”
Section: Biochemical Confirmationmentioning
confidence: 99%
“…The fluorogenic substrate 4-methylumbelliferyl 2-acetamido-2deoxy-,/-D-glucopyranoside was used to measure fl-hexosaminidase activity [14]. Iduronate-2-sulphatase (IDS) [15], a-L-Iduronidase [16] and N-acetylgalactosamine-4-sulphatase (4S) [17] were assayed by previously reported procedures.…”
Section: Assay Of Other Lysosomal Enzyme Activitiesmentioning
confidence: 99%